Alex Wiseman: reluctant architect? - Addison, Paul (Architectural History Aotearoa, 2017)
The Auckland Ferry Building, completed in 1912, is still a significant landmark in downtown Auckland today. However, its architect, Alex Wiseman, remains less well-known and more enigmatic. Born in Auckland in 1865 into a prominent Methodist family, Wiseman was apprenticed at 16 years of age to noted architect Edward Bartley for a term of four years. Wiseman then practised as a draughtsman for a period, before moving to Victoria, Australia, to follow his first love, music, making his living as a music teacher and organist. After marrying and starting a family, the lot of an impecunious musician may have held less appeal, and in 1903 Wiseman returned to Auckland. He established his own architectural practice and, over the next 12 years until his death at the age of just 50, he received, often with the aid of familial and church connections, several high-profile commissions, including the ferry building, the YMCA building and Auckland Training College (both in Wellesley Street), and "Greenacres," the home of James Gunson, later mayor of Auckland.